Transparency, Trade Costs, And Regional Integration In The Asia Pacific - Helble, Matthias (The World Bank, 2007)
The authors show in this paper that increasing the transparency of the trading environment can be an important complement to traditional liberalization of tariff and non-tariff barriers. Our definition of transparency is grounded in a transaction cost analysis. The authors focus on two dimensions of transparency: predictability (reducing the cost of uncertainty) and simplification (reducing information costs). Using the Asia Pacific Economic Cooperation (APEC) member economies as a case study, the authors construct indices of importer and exporter transparency for the region from a wide range of sources. Our results from a gravity model suggest that improving trade-related transparency in APEC could hold significant benefits by raising intra-APEC trade by proximately USD 148 billion or 7.5 pecent of baseline trade in the region